HISTORY OF THE STUDY OF EXPLANATORY CONSTRUCTIONS IN UKRAINIAN LINGUISTICS - Новікова, Ольга (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
The lack of a clear definition of the notion of explanation in the linguistic scientific literature leads to an appeal to the evolution of the formation of views about this category, actualizes the attempt to determine the status of the category of explanation, the means of implementation of which are commensurate with the means of implementation of categories of refinement, separation, semi-prediction, indirect mediating analysis and requires a consistent delineation of these syntactic units. Exploration of explanatory constructs in a simple complicated sentence has been carried out taking into account the achievements of both Ukrainian linguistic and linguistics in general. Issues of explanatory constructions were raised in their writings by I. O. Aksenova, T. A. Alexandrova, I. M. Aribzhanova, N. S. Valgina, I. R. Vychovanets, M. O. Vintonov, S. M.Glazova, K. G. Gorodenska, L. V. Zakharova, O. P. Kadochnikova, E. V. Krotevych, M. Y. Pliushch, A. F. Pryjatkina, O. G. Rudnev, I. I. Slynko, M. M. Shansky and others. Purpose. To comprehensively analyze the dynamics of the formation of explanatory structures in linguistic studies, to determine their differential and classification features. Results. In the works of the first half of the nineteenth century there was no coherent theory of explanatory terms. In the scientific studios of that time, the concept explanatory terms was not used in general, but are used by the term separate members of the sentence, identifying it with an appendix (F. I. Buslajev, O. A. Potebnya). In the writings of 70-80 years of the XIX century. Scientist’s views on defining the specimen were changed. Its main feature is considered not attributive, but explanatory, clarifying functions. Scientists distinguish notions of appendix and separation as separate syntactic categories (O. M. Peshkovsky, E. V. Krotevich, B. M. Kulik). In the second half of the twentieth century. the notions of attachment and separation are finally included in linguistic science as separate syntactic categories. In the future, linguists are stepping up their attention to the separation of subordinate clauses of the sentence, in particular, in-depth exploration of the explanatory and refinement functions of separation, emphasize the need to distinguish refinement structures as a separate category, establish the differences between explanatory and refinement units. Originality. The formation of the category of explanation in Ukrainian linguistics, the role of syntactic constructions with the meaning of explanation and clarification in a simple non-elementary sentence, the features of their differentiation, specifics and purposes are analyzed. Conclusion. Analyzing the works of leading syntaxists, we can confidently speak about the need to differentiate the concepts of explanation and refinement (T. A. Alexandrova, N. S. Valgina, I. R. Vyhovanets, L. V. Zakharova, A. F. Pryyatkina, I. I. Slуnko, N. M. Shansky). In scientific studies of the late twentieth century – beginning of the XXI century a detailed explanation of the differentiation of explanatory, semi-predictive and syntactically mediated constructions is given (I. O. Aksenova, I. R. Vyhovanets, M. O. Vintonov, K. G. Gorodenska, N. V. Gujvanіuk, O. P. Kadochnikova, M. F. Kobylianska, I. I. Sniveler). Today, linguists continue to research explanatory constructs, stufy out discussion questions, and clarify the scope of this concept.